DETERMINATION OF THE ANTIOXIDANT ACTIVITY OF MICROCLONES OF WALNUT (JUGLANS REGIA L.) - Korbozova, N.K.; Yerbai, M.; Zorbekova, A.N.; Aisanbayeva, A.E.; Terletskaya, N.V. (Eurasian Journal of Applied Biotechnology, 2025)
Walnut (Juglans regia L.), a plant belonging to the genus Juglans of the family Juglandaceae, native to the region extending from the Balkans east to the Himalayas. Since ancient times, walnut has been widely used in both folk and traditional medicine for various diseases and is among the medicinal plants of interest due to its rich content of antioxidants such as flavonoids, phenolic acids, melatonin, folate, gamma-tocopherol, selenium and proanthocyanidins in various organs (kernels, shells, roots and leaves). However, until now there have been virtually no studies on how walnut can respond to abiotic stresses in vitro culture and what benefits such a study can provide, so our work is devoted to the analysis of the antioxidant activity of J. regia shoot microclones in vitro after exposure to low positive temperatures. The results of this work show that Juglans regia effigia microclones subjected to cold stress have greater antioxidant potential than microclones grown under more favorable temperature conditions.